*-koatē/-škoatē inchoative verbs in Skolt and Kola Saami dialects - Kuokkala, Juha (Zenodo, 2019)
The file contains two sets of data concerning * -koatē/-škoatē inchoative verbs in Skolt and Kola Saami dialects. The first one is a schematic representation of the verbs found in KKLS [1] (alphabetical span of A–K) with a focus on the derivational variants * -koatē vs. * -škoatē . Two versions are presented on separate sheets, one with a single alphabetical listing and another with grouping according to the (original) syllable count of the verb base. The columns P.V code the variants occurring in different dialects (codes: k = *-koatē, s = *-škoatē, ks = both). [1] KKLS = T. I. Itkonen 1958: Koltan- ja kuolanlapin sanakirja. Wörterbuch des Kolta- und Kolalappischen . I–II. Helsinki: Société Finno-Ougrienne. The second data set contains the * -koatē/-škoatē verb lexemes found in Szabó 1968 and 1987 [2, 3]. The data is grouped according to (original) syllable count, suffix variant (* -koatē vs. * -škoatē ) and language area (Kildin vs. Ter [Turja]). Only one occurrence of each derivative lexeme is quoted. [2] Szabó, László 1968: Kolalappische Volksdichtung (Texte aus den Dialekten in Kildin und Ter) . Zweiter Teil nebst grammatischen Aufzeichnungen. Göttingen: Vandenhoeck & Ruprecht. [3] Szabó, László 1987: The use of the inchoative in Kola-Sami sentences. – Nordlyd 13: 70–103. This is a data set supplement of: Kuokkala, J. (2019). Saami - (š)goahti inchoatives: their variation, history, and suggested cognates in Veps and Mordvin. Suomalais-Ugrilaisen Seuran Aikakauskirja 97, 153–181. https://doi.org/10.33340/susa.75718